Proyección de la demanda, cambio de transformador de potencia y migración de cargas en la Compañía Alimenticia Agua Santa “ALIAGUASANTA” CIA. LTDA. del cantón Salcedo - Suárez Mullo, Pablo Javier (2023)
This work is part of the research project related to demand projection, power transformer changer and migration at Compañía Alimenticia Agua Santa “ALIAGUASANTA” CIA. LTDA. In the Salcedo canton, where there were problems in terms of energy supply and power quality; As a first step, it was necessary to carry out a total information survey to know the current situation of the company, the total installed load, determining that it was higher than the capacity of the transformer, even though the reserve loads were omitted from the analysis, after this task, the design of the single-line plans of the electrical distribution of the entire company was carried out to have a better overview of the distribution system. In addition, two network analyzers were installed to determine energy consumption, power, voltages, currents and evaluate the level of transformer overload, obtaining as a result that the transformer installed in several periods of time was working over the limit of its rated capacity.